2021
DOI: 10.1017/s0950268821001291
|View full text |Cite
|
Sign up to set email alerts
|

Serious complications in COVID-19 ARDS cases: pneumothorax, pneumomediastinum, subcutaneous emphysema and haemothorax

Abstract: The novel coronavirus identified as severe acute respiratory syndrome-coronavirus-2 causes acute respiratory distress syndrome (ARDS). Our aim in this study is to assess the incidence of life-threatening complications like pneumothorax, haemothorax, pneumomediastinum and subcutaneous emphysema, probable risk factors and effect on mortality in coronavirus disease-2019 (COVID-19) ARDS patients treated with mechanical ventilation (MV). Data from 96 adult patients admitted to the intensive care unit with COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
35
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 33 publications
(68 reference statements)
2
35
2
1
Order By: Relevance
“…1 They are also frequently reported in mechanically ventilated patients with acute respiratory distress syndrome (ARDS) and severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) infection, which was first reported in Wuhan, Hubei Province, China, in December 2019. [2][3][4][5] The incidence of SP or SPM (SP-SPM) in patients with COVID-19, the respiratory disease caused by SARS-CoV-2, is currently unknown. A large study by Miró et al 6 reported a small number of patients with SP and COVID-19, with an incidence of less than 1‰.…”
Section: Introductionmentioning
confidence: 99%
“…1 They are also frequently reported in mechanically ventilated patients with acute respiratory distress syndrome (ARDS) and severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) infection, which was first reported in Wuhan, Hubei Province, China, in December 2019. [2][3][4][5] The incidence of SP or SPM (SP-SPM) in patients with COVID-19, the respiratory disease caused by SARS-CoV-2, is currently unknown. A large study by Miró et al 6 reported a small number of patients with SP and COVID-19, with an incidence of less than 1‰.…”
Section: Introductionmentioning
confidence: 99%
“…In our series, hemothorax was related to iatrogenic factors such as chest tube placement, thoracentesis or previous surgery in 11 patients. The remaining two patients underwent spontaneuos hemothorax or, more likely, it was due to mechanical ventilation, as already described in the literature ( 31 ).…”
Section: Discussionmentioning
confidence: 83%
“…Additionally, non-survivors had more days of hospital stay, who had a median of 20 days, compared to those survivors, who had a median of 19 days. It has been reported that IMV use in patients with severe ARDS is related to the presentation of complications such as alveolar injury, which prolongs their hospital stay [ 13 ]. Regarding the outcome, the non-survivors had a higher frequency of requirements of IMV (93.0%) compared to survivors (60.9%).…”
Section: Discussionmentioning
confidence: 99%